Mesenchymal stromal cells, metabolism, and mitochondrial transfer in bone marrow normal and malignant hematopoiesis - Singh, Abhishek K.; Prasad, Parash; Cancelas, Jose A. (Frontiers in Cell and Developmental Biology, 2023)
Hematopoietic stem cell (HSC) transplantation-based treatments are in different phases of clinical development, ranging from current therapies to a promise in the repair and regeneration of diseased tissues and organs. Mesenchymal stromal/stem cells (MSCs), which are fibroblast-like heterogeneous progenitors with multilineage differentiation (osteogenic, chondrogenic, and adipogenic) and self-renewal potential, and exist in the bone marrow (BM), adipose, and synovium, among other tissues, represent one of the most widely used sources of stem cells in regenerative medicine. MSCs derived from bone marrow (BM-MSCs) exhibit a variety of traits, including the potential to drive HSC fate and anti-inflammatory and immunosuppressive capabilities via paracrine activities and interactions with the innate and adaptive immune systems. The role of BM-MSC-derived adipocytes is more controversial and may act as positive or negative regulators of benign or malignant hematopoiesis based on their anatomical location and functional crosstalk with surrounding cells in the BM microenvironment. This review highlights the most recent clinical and pre-clinical findings on how BM-MSCs interact with the surrounding HSCs, progenitors, and immune cells, and address some recent insights on the mechanisms that mediate MSCs and adipocyte metabolic control through a metabolic crosstalk between BM microenvironment cells and intercellular mitochondrial transfer in normal and malignant hematopoiesis.